Peter and the shadow thieves - Barry, Dave.; Pearson, Ridley; Call, Greg (New York : Hyperion Paperbacks for Children, 2006)
Realizing that Molly and the other Starcatchers are in danger when the sinister being Lord Ombra visits the island and seems to control people through their shadows, Peter and Tinker Bell travel to England to help save the stardust.
780
Accelerated Reader AR
Keywords: Shadows -- Fiction; Adventure and adventurers -- Fiction; Characters in literature -- Fiction; Humorous stories